Resilience and Management Control Systems in Agribusiness Companies: A Case Study of PT Pandu Karya Aksara - Shinta J. C. Wangke; Yunita Mandagie; Emilia M. Gunawan (Return : Study of Management, Economic and Bussines, 2024)
Despite the abundance of research focused on firm resilience, there are still very few studies that analyze internal mechanisms to see what generates resilience capacity in agribusiness firms. Considering the Management Control System (SPM) as a driver of organizational change, this study aims to analyze the role of SPM as a determinant of resilience in agribusiness companies with a case study on PT Pandu Karya Aksara. This study uses a qualitative method with a case study approach. The data collected consisted of primary data and secondary data. Primary data was obtained from semi-structured interviews, while secondary data was obtained from observation and analysis of documents. This research provides benefits for the development of science and insights in supporting adaptive behavior and assisting effective decision-making, so that companies can improve competitiveness and efficiency.  This research shows how resilience is generated and strengthened through SPM, when companies are faced with various challenges, such as fluctuations in commodity prices, climate change, market uncertainty, and regulatory changes.